IMPACT OF COVID-19 PANDEMIC ON THE USE OF RAIL TRANSPORT SERVICES IN SLOVAKIA (Perner's Contacts, 2022)
This paper deals with the impact of measures introduced in the first half of 2020 on rail passenger transport in the Slovak Republic in order to slow down the spread of the virus during the first wave of the COVID-19 pandemic. The paper contains a chronological list of measures introduced by carriers and infrastructure managers during the first wave of the pandemic in rail transport. The main objective of the paper is to investigate and analyze the drop in transport performance in each month of the first half of 2020 and the subsequent estimation of the impact of these changes on the passenger rail sector. The transport performance is then analyzed during three important transport sessions in the Slovak Republic, comparing the years 2018, 2019, and 2020.
Keywords: pandemic COVID-19; transport performance; measures